Peningkatan Keaktifan Kerja Kelompok Melalui Model Problem Based Learning Berbasis Outdoor Study Siswa Kelas IV SDN Sarikarya Yogyakarta - Nurani, Resti; Legowo, Anton (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
The purpose of conducting this research is to increase the activeness of group work through the Problem Based Learning model based on Outdoor Learning in class IV with the subject of Pancasila Education (PP) at SD Negeri Sarikarya Yogyakarta. The research carried out applies the type of Classroom Action Research (CAR). Sources of data are educators and students as research subjects. The data collection instruments used in this study were interviews, observations and questionnaires. Data collection was carried out in three cycles, namely pre-cycle, cycle I, and cycle II. The data analysis technique is descriptively taken from the percentage of active group work. Based on the results of the research that has been carried out, it can be concluded that the use of the Outdoor Study-based Problem Based Learning learning model is able to increase the activity of students in group work for class IV SD Negeri Sarikarya. In the pre-cycle implementation, the average activity of students in group work was 54.5. The data generated in the first cycle there was an increase of 15.4 to 69.9 and was included in the fairly active criteria. Because the results were not appropriate, it was continued in cycle II and showed an increase of 18.8 to 88.7 and was included in the Very Active criteria. From the increased activity data obtained, it can be seen that there has been an increase in activity starting from the pre-cycle stage, cycle I to cycle II.